PRICE STRATEGY ANALYSIS ON INCREASING THE SALES VOLUME OF CCTV PRODUCTS IN CV. ANUGERAH JASA ABADI BANDUNG CITY - Cintya Elsa Nurjanah; Regita Widia Insani; Tiris Sudrartono (Jurnal Ekonomi, 2022)
This study aims to find out how much the price strategy is related to the sales volume of CCTV by using 7 dimensions of the price strategy, namely the statement of the value of a product, Aspects that are clear to buyers, the main determinants of demand, Directly related to income and prices, Flexibility, Influence image and positioning and Trigger internal conflicts, distribution channels, competitors, government agencies and public policies. The research population is all users who have bought CCTV at CV. Anugerah Jasa Abadi Bandung City in 2021, the total population is 365 buyers and the sample has been determined based on the solvin formula, namely 78 respondents to be given a questionnaire. Based on the research results, by following market prices and providing discounts so that they can attract consumers to buy at CV. Anugerah Jasa Abadi Bandung City.